1997
DOI: 10.1111/j.1532-5415.1997.tb02965.x
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease and Driving: Prediction and Assessment of Driving Performance

Abstract: Inasmuch as all subjects except one were still driving and all wished to continue to drive, it is important to note that 63.2% of subjects failed the on-road evaluation. Conversely, 36.8% were judged safe to drive, suggesting that AD diagnosis alone may be insufficient criteria for cessation of driving. A standardized road test may be the only appropriate means of determining driving competence in people diagnosed with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 18 publications
2
108
1
2
Order By: Relevance
“…At the time of the study, 30% of the sample subjects continued to drive for 3.6 years following diagnosis. Fox and others reported that their study subjects were driving an average of 4 years (SD 2.0) following diagnosis (16). In a study by Bedard and colleagues, the mean interval between the onset of symptoms and a clinical assessment that included information about patients' driving history was 5.5 years (95%CI, 5.2 to 5.8 years) (17).…”
Section: )mentioning
confidence: 99%
“…At the time of the study, 30% of the sample subjects continued to drive for 3.6 years following diagnosis. Fox and others reported that their study subjects were driving an average of 4 years (SD 2.0) following diagnosis (16). In a study by Bedard and colleagues, the mean interval between the onset of symptoms and a clinical assessment that included information about patients' driving history was 5.5 years (95%CI, 5.2 to 5.8 years) (17).…”
Section: )mentioning
confidence: 99%
“…45,46,[56][57][58] These studies may be confounded because of the failure to control for the amount of mileage actually driven, lack of control groups, small sample size, method of reporting and avoidance of high risk driving situations. [44][45][46]51,59 Overall, the evidence does support an increased risk of motor vehicle collisions in patients with dementia even with restrictions attached to driving, such as driving distance or location. 51,60-62…”
Section: Collision Ratementioning
confidence: 99%
“…49 In some small studies, the MMSE has not been found to be a reliable method of predicting driving performance. 44,50 Since this tool was not originally designed to assess cognitive function with respect to driving, the MMSE as a measure to assess driving performance lacks validity when used to assess patients falling between the extremes of cognitive impairment. 7,51 The Useful Field of View (UFOV) is a computer-administered test that measures and detects abnormalities in the speed of visual processing and sensory function.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
See 2 more Smart Citations